Juvenile Court Statistics, 1988: (United States) ([Verlag nicht ermittelbar], 1994)
This data collection describes in quantitative terms the volume of juvenile cases disposed in 1988 by courts having jurisdiction over juvenile matters (delinquency, status offense, and dependency cases). Inaugurated in 1926 to furnish an index of the problems brought before the juvenile courts, this series is the oldest continuous source of information on the processing of delinquent and dependent youth by juvenile courts. Information is provided on state, county, number of delinquency cases by sex, number of status offense cases by sex, number of dependency cases by sex, and total number of cases by sex.